Pengaruh Sistem Informasi Akuntansi, Gaya Kepemimpinan, Dan Komitmen Organisasi Terhadap Kinerja Karyawan PT. Bank Rakyat Indonesia Cabang Denpasar (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
This research aims to examine the influence of accounting information systems, leadership style and organizational commitment on the performance of PT. Bank Rakyat Indonesia Denpasar. The theory used in this research is Stewardship Theory. The population in this study were all employees at PT. Bank Rakyat Indonesia Denpasar. Where the sample that meets the research criteria is 70 respondents with a sample determination technique using purposive sampling. Data collection was carried out using the questionnaire method. The data analysis technique used is multiple linear regression analysis. The research results show that the accounting information system, leadership style and organizational commitment have a positive effect on the performance of PT. Bank Rakyat Indonesia Denpasar.